Observation of Fast Low‐Temperature Oxygen Ion Conduction in CeO2/β"‐Al2O3 Heterostructure - Yingbo Zhang; Decai Zhu; Zhonglong Zhao; Jiamei Liu; Yuzhao Ouyang; Jiangyu Yu; Zhongqing Liu; Xixi Bai; Nan Wang; Lin Zhuang; Wuming Liu; Chengjun Zhu (Advanced Science)
Abstract Semiconductor ion fuel cells (SIFCs) have demonstrated impressive ionic conductivity and efficient power generation at temperatures below 600 °C. However, the lack of understanding of the ionic conduction mechanisms associated with composite electrolytes has impeded the advancement of SIFCs toward lower operating temperatures. In this study, a CeO2/β″‐Al2O3 heterostructure electrolyte is introduced, incorporating β″‐Al2O3 and leveraging the local electric field (LEF) as well as the manipulation of the melting point temperature of carbonate/hydroxide (C/H) by Na+ and Mg2+ from β″‐Al2O3. This design successfully maintains swift interfacial conduction of oxygen ions at 350 °C. Consequently, the fuel cell device achieved an exceptional ionic conductivity of 0.019 S/cm and a power output of 85.9 mW/cm2 at 350 °C. The system attained a peak power density of 1 W/cm2 with an ultra‐high ionic conductivity of 0.197 S/cm at 550 °C. The results indicate that through engineering the LEF and incorporating the lower melting point C/H, there approach effectively observed oxygen ion transport at low temperatures (350 °C), effectively overcoming the issue of cell failure at temperatures below 419 °C. This study presents a promising methodology for further developing high‐performance semiconductor ion fuel cells in the low temperature range of 300–600 °C.